Professional Chaplaincy and Clinical Pastoral Education Should Become More Scientific: Yes and No - Pye, Jonathan (Implicit religion, 2008)
The article reviews the book "Professional Chaplaincy and Clinical Pastoral Education Should Become More Scientific: Yes and No," by Larry Vandecreek.